Analisis Perbandingan Kinerja Berdasarkan Kesetaraan Gender Pada PT. Astra International, Tbk. – Daihatsu Sentra Manado (Studi Pada Karyawan Bagian Marketing) - Kamasi, Valencia; Areros, William Agustinus; Runtuwene, Roy F. (JURNAL ADMINISTRASI BISNIS, 2019)
This study aims to see whether there are significant differences in performance based on gender equality in female employees and male employees in the marketing division of PT. Astra International, Tbk. - Daihatsu Sentra Manado. The population of this study is all employees of the marketing division of PT. Astra International, Tbk. - Daihatsu Sentra Manado, which consists of 51 employees, consisting of 36 male employees and 15 female employees. The sampling technique used is the census technique, which is to take from all existing populations to be sampled. Where there were 15 female employees and 15 male employees were taken to balance the sample of female employees. So the total sample in this study was 30 employees. Based on the results of descriptive statistical analysis, the average value for the performance of male and female employees is equally higher than the minimum value available. Although not large, the results of this study indicate that the average value of male employee performance is higher than that of overall female employees. From the results of the independent sample t-test statistical test, a significant value gives a result stating that H0 is accepted. The results of this study state that there is no significant difference in performance between male employees and female employees in the marketing department based on gender equality.